Determinants of Information Use Pattern in Higher Education - Devadhas, T. (Asian Journal of Managerial Science, 2014)
This paper aims at analyzing the determinants of information use pattern in higher educational institution. Information seeking behaviour has become one of the basic necessities of human life, especially in the modern informatics world. Everyone needs information for various purposes. In fact, almost all activities depend on information in the regional, national and international level. The role and impact of information seeking pattern occupy vital role in higher education. In fact, students of higher education use information to enrich knowledge in the field of their own interest. However,there are factors which determine the information use pattern in higher educational institutions. It is interesting to note that in Kanyakumari district of Tamilnadu all kind of educational facilities are available except law and veterinary science. People give more importance to higher education. Hence, an attempt has been made to discern the determinants of information use pattern in Kanyakumari district of Tamilnadu.